“Internet of Things Enabled Healthcare Kit” - Mr. Antim Dev Mishra, Dr Naveen Nandal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The Internet of Things (IoT) is a network of intelligent heterogeneous objects that can communicate and share the data. Patients are required to attend the doctor on a daily basis in traditional models of healthcare. Both the patient and the medical personnel can find these traditional procedures inconvenient. The aim of this project is to create a smart IoT-based health monitoring system which have non-invasive sensors to read various health parameters and displays them on an LCD module in real time. The user can also transfer the data to the cloud to be safely stored and can share this data with doctor for treatment. Data can be live viewed from any location on the planet. Since the battery capacity of each system used in this project is minimal, it would reduce the power usage in order to prolong the life of the healthcare kit. The IoT-based hospital healthcare kit developed using an Arduino Uno, ESP8266, pulse rate sensors, blood oxygen sensor, ECG sensor, blood pressure sensor, and temperature sensor is described in this paper. As a result, IoT-enabled systems improve treatment delivery while also lowering costs by continuously collecting and analysing data.